Association between inflammatory potential of the diet and sarcopenia/its components in community-dwelling older Japanese men. (November 2021) - Son, Bo-Kyung; Akishita, Masahiro; Yamanaka, Takashi; Toyoshima, Koichi; Tanaka, Tomoki; Suthutvoravut, Unyaporn; Iijima, Katsuya
Highlight: Highest tertile of the E-adjusted DII in men showed a 2.89-times higher risk of sarcopenia than those in the lowest tertile. Men with lower anti-inflammatory properties scored higher E-adjusted DII and were significantly associated with sarcopenia. Higher serum hsCRP levels were seen in sarcopenic men with the highest E-adjusted DII. Anti-inflammatory diet might be one of preventive strategies for sarcopenia. Abstract: Purpose: Chronic inflammation is a pathophysiological cause of age-related diseases including sarcopenia. However, limited data are available on the association between the diet-derived inflammation and sarcopenia. Here, using the Dietary Inflammatory Index (DII), we examined the associations between inflammatory potentials of the diet, sarcopenia/its components, and serum inflammatory markers. Materials and methods: This cross-sectional study was performed in 2014 among 1, 254 community-dwelling older adults. Energy-adjusted DII score (E-adjusted DII) was calculated using a self-administered diet history questionnaire. Sarcopenia/its components was determined according to the Asian Working Group for Sarcopenia. Serum interleukin (IL)-1β, IL-4, IL-6, IL-10, tumor necrosis factor (TNF)α, and high-sensitivity C-reactive protein (hsCRP) were measured. Results: The mean of E-adjusted DII was 0.13±2.1 (-4.92 5.29) in participants (74.6±5.5 y). After adjustment of confounders, men in the highest tertile of the E-adjusted DII showed a 2.89-times (95% CI: 1.04-8.04) higher risk of sarcopenia than those in the lowest tertile. Regarding its components (low muscle mass/strength/function), men in the highest tertile did not have significantly greater odds, respectively. Intriguingly, when the E-adjusted DII was calculated only based on anti-inflammatory food parameters, men who did not consume food with anti-inflammatory properties scored high E-adjusted DII and were significantly associated with sarcopenia in the highest tertile (OR: 2.96; 95% CI: 1.06-8.93). Higher serum hsCRP levels were seen in sarcopenic men with the highest E-adjusted DII (p=0.036). Conclusions: These results suggest that a diet with pro-inflammatory potential is associated with the risk of sarcopenia. Further investigations whether anti-inflammatory diet could reduce its risk are needed.